Analysing individual racism portrayal in Hanna Alkaf’s novel The Weight of Our Sky - Shue Wenn Yeoh; Mansour Amini; Kam-Fong Lee; Hu Oumeng (Cogent Arts & Humanities)
This study analyzes Hanna Alkaf’s novel The Weight of Our Sky, concentrating on individual racism within the socio-historical context of Malaysia during the May 13, 1969, incident. Through thematic analysis, the study uncovers how Alkaf illustrates racial discrimination via the characters’ behaviors, interactions, and internal conflicts. The depiction of individual racism in the novel encompasses overt and subtle forms of prejudice, although it does not extensively delve into systemic issues. The paper investigates the methods of implicit and explicit characterization, particularly in the protagonist who grapples with OCD, showcasing Melati’s psychological struggles. The findings highlight that individual racism manifests in overt hate speech, social ostracism, and internalized prejudice, all illustrating significant societal divisions. Derogatory language used by characters emphasized the normalization of racial animosity in daily interactions. The study also identifies the development of resilience in the face of racial violence, which contributes to personal growth. The coping mechanisms and resolution of conflicts within the narrative emphasize personal triumph rather than a comprehensive social critique. This study acknowledges the novel’s strengths, including its sensitive portrayal of mental health and cultural elements, concluding that the work serves as a powerful educational tool offering valuable lessons in perseverance, problem-solving, and conflict resolution.